Testing formal pragmatics of questions through their ignorance inferences - Zhao, Zhuoye; Cremers, Alexandre (Proceedings of the Amsterdam Colloquium, 2019)
Questions are well-studied in semantics, including from a psycholinguistics perspective. They also play a key role in pragmatics through questions under discussions, which are known to affect a wide range of phenomena (e.g., focus, implicatures). The pragmatics of questions themselves however is largely understudied, with very few theoretical proposals and only a handful of experimental studies. Pragmatics studies how speakers choose an utterance over possible competitors, and how listeners can draw complex inferences by reconstructing the speaker’s reasoning leading to this choice. While we have a good understanding of the factors at play when a speaker utters a declarative sentence, much less is known about questions. The goal of this paper is to test two proposals extending Grice’s Maxims to questions: van Rooij’s entropy as a measure of question utility, and Groenendijk and Roelofsen’s inquisitive pragmatics. The two theories make opposite predictions regarding the choice between polar and wh-questions in ignorance and partial knowledge situations, and therefore the implicatures they give rise to regarding the questioner’s knowledge. The results of two experiments corroborate the predictions of van Rooij’s proposal. In passing, we establish that the cornering effect of negative alternative questions (Biezma 2009) is independent from their ignorance requirements.